Dosis de fertilizante nitrogenado y su efecto en el rendimiento y captura de carbono del forraje Morus nigra L. “Morera” en Iquitos - Perú – 2020 - Ruiz Ruiz, Emil Samir (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Vacunos Project in the Zungarococha Farm, entitled "DOSE OF NITROGEN FERTILIZER AND ITS EFFECT ON THE YIELD AND CARBON CAPTURE OF FORAGE Morus nigra L . "Morera" IN IQUITOS - PERU - 2020. The evaluations were carried out 60 days after sowing with plots of 3 mx 1.2 m (3.6 m2) and an experimental area of 170 m2. With a Random Complete Block Design (DBCA), with five treatments and four repetitions, the treatments under study were: T0 (0 kilos of nitrogen / ha), T1 (45 kilos of nitrogen / ha), T2 (90 kilos of nitrogen / ha) nitrogen / ha), T3 (135 kilos of nitrogen / ha) and T4 (180 kilos of nitrogen / ha), obtaining the following results: With the T4 treatment (180 kilos of nitrogen / ha) it was possible to increase the averages of the height of plant (m), green matter (gr / m2), dry matter (gr / m2), the yields of green matter in Kg / plot and Kg / ha, and the yields of kg / ha of C and CO2. In this sense, it was shown that the doses of nitrogen fertilizer favorably influence the yield and carbon sequestration of Morus nigra L. forage. According to what was found in this work, a higher dose of nitrogen fertilizer results in improvements for the performance of the pasture forage and in the carbon capture.